odpoveď:
# (Dy) / (dx) = 2 (2x + 5) (x ^ 2 + 5x) 6 (3 x ^ 2-5) (x ^ 3-5x) ^ 2 #
vysvetlenie:
Pravidlo reťazca: # (Dy) / (dx) = (dy) / (du) * (du) / (dx) #
Robíme to dvakrát na odvodenie oboch # (X ^ 2 + 5 x) ^ 2 # a # 2 (x ^ 3-5x) ^ 3 #
# D / (dx) (x ^ 2 + 5 x) ^ 2 #: Nechajme # U = x ^ 2 + 5x #, potom # (Du) / (dx) = 2x + 5 #
# (Dy) / (du) = 2 (x ^ 2 + 5 x) #
tak # (Dy) / (dx) = 2 (2x + 5) (x ^ 2 + 5 x) #
# D / (dx) 2 (x ^ 3-5x) ^ 3 #: Nechajme # U = x ^ 3-5x #, potom # (Du) / (dx) = 3x ^ 2-5 #
# (Dy) / (du) = 6 (x ^ 3-5x) ^ 2 #
tak # (Dy) / (dx) = 6 (3 x ^ 2-5) (x ^ 3-5x) ^ 2 #
Teraz pridávame obidva, # (Dy) / (dx) = 2 (2x + 5) (x ^ 2 + 5x) 6 (3 x ^ 2-5) (x ^ 3-5x) ^ 2 #